PERANGKAT LUNAK SIMULASI DEADLOCK MENGGUNAKAN ILUSTRASI DINING PHILOSOPHERS PROBLEM - Arfiani Nur Khusna; Nur Rochmah Dyah PA (JURNAL INFORMATIKA DAN KOMPUTER, 2017)
The operating system must be able to control resource usage. In the process of designing the operating system, there is a common foundation called kongkurensi. Processes called kongkuren if processes (more than one process) are at the same time. This is called the multitasking operating system. Kongkuren processes can be completely independent of the other but can also interact with each other. Processes that require synchronization in order to interact properly controlled. However, the processes that interact kongkuren, there are problems to be solved such as deadlock and synchronization. Deadlock occurs because a set of processes in a block where every process of bringing a resource and waiting to get the resources brought by another process so there is a wait state which will never expire (deadlock).Dining Philosophers Problem is an illustration of the possibility of a deadlock, a condition in which two or more processes can not continue its execution as they waited for the use of resources. Dining Philosophers problem can be illustrated, there are five philosophers sitting around a table. Five philosophers is an illustration of the five processes with the state of the process of mutual waiting to use the resources.The results of this study are to describe the state of software deadlocks using illustrations dining philosophers problem with illustrations of all the philosophers were in a state of hunger and holding chopsticks in hand to the left, there will be a deadlock condition.Keywords: deadlock, dining philosophers problem, simulation